The ethnogenesis of the Kazakh dance - Balzhan S.Tleubayeva, Ylduz A. Saparova, Seraly Sh. Tleubayev, Aigul K. Kulbekova,; Asia G. Isengaliyeva, Dina Y. Kabdusova, Gulmira R. Dildebaeva, (Opción, 2019)
The article considers fundamental issues of traditional culture as an integral social-cultural phenomenon via a complex of complementary research methods namely, the analysis of the exemplars of the traditional folk music creative activity and the analysis of the artistic-aesthetic features of dances. The article provides a general analysis of the influence of epos, everyday life, customs and traditions upon the development of the Kazakh dance themes. We can conclude that the Kazakh folk dance is based on the traditional Kazakh culture which originates from the reflection of the reality through the folk cultural-philosophical wisdom.